2017
DOI: 10.3390/md15100297
|View full text |Cite
|
Sign up to set email alerts
|

Hypopigmenting Effects of Brown Algae-Derived Phytochemicals: A Review on Molecular Mechanisms

Abstract: There is a rapid increase in the demand for natural hypopigmenting agents from marine sources for cosmeceutical and pharmaceutical applications. Currently, marine macroalgae are considered as a safe and effective source of diverse bioactive compounds. Many research groups are exploring marine macroalgae to discover and characterize novel compounds for cosmeceutical, nutraceutical, and pharmaceutical applications. Many types of bioactive secondary metabolites from marine algae, including phlorotannins, sulfated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 106 publications
0
42
0
Order By: Relevance
“…They also demonstrated that the pigmentation in the guinea pigs was suppressed by a daily consummation of fucoxanthin of about 0.001% through their diet [39,48]. Furthermore, the oral treatment of fucoxanthin can inhibit transcription for melanogenesis by repressing mRNA expression of COX-2, p75NTR, EP1, and MC1R [39]. The findings showed that fucoxanthin has anti-pigmentary effect by suppressing prostaglandin E2 synthesis and melanogenic stimulant receptors [39,48].…”
Section: Anti-melanogenic Activitymentioning
confidence: 96%
See 2 more Smart Citations
“…They also demonstrated that the pigmentation in the guinea pigs was suppressed by a daily consummation of fucoxanthin of about 0.001% through their diet [39,48]. Furthermore, the oral treatment of fucoxanthin can inhibit transcription for melanogenesis by repressing mRNA expression of COX-2, p75NTR, EP1, and MC1R [39]. The findings showed that fucoxanthin has anti-pigmentary effect by suppressing prostaglandin E2 synthesis and melanogenic stimulant receptors [39,48].…”
Section: Anti-melanogenic Activitymentioning
confidence: 96%
“…Interestingly, they found that fucoxanthin suppressed tyrosinase-related protein 1 (TRP1) instead of tyrosinase. They also demonstrated that the pigmentation in the guinea pigs was suppressed by a daily consummation of fucoxanthin of about 0.001% through their diet [39,48]. Furthermore, the oral treatment of fucoxanthin can inhibit transcription for melanogenesis by repressing mRNA expression of COX-2, p75NTR, EP1, and MC1R [39].…”
Section: Anti-melanogenic Activitymentioning
confidence: 97%
See 1 more Smart Citation
“…The KIT receptor activates the cAMP pathway and MC1R activates both cAMP and ERK pathway which further phosphorylates the MITF. This leads to the expression of tyrosinase-related enzymes which further mediates the production of melanin [22][23][24][25][26]. The skin under UV generates the reactive oxygen species (ROS) that activate the α-MSH and MC1R and enhances the production of tyrosinase that leads to the excess generation of melanin [27,28].…”
Section: Hyperpigmentationmentioning
confidence: 99%
“…1 O 2 is the main reactive oxygen molecule responsible for UV light-induced photooxidative damage of photosynthetic membranes and animal tissues. The strong ability of carotenoids to quench 1 O 2 has been suggested as the main mechanism by which they afford their beneficial effects on skin protection (Azam et al, 2017;Corinaldesi et al, 2017). Carotenoids can also Health impact of marine carotenoids Miyashita et al scavenge free radicals.…”
Section: Introductionmentioning
confidence: 99%